The 100 Greatest Silent Film Comedians - Roots, James (Rowman & Littlefield Publishers, 2014)
The silent film era featured some of the most revered names of on-screen comic performance, from Charlie Chaplin and Buster Keaton to Harold Lloyd, Douglas Fairbanks, and Laurel & Hardy. Besides these giants of cinema, however, there are other silent era performers—both leading actors and supporting players—who left an enduring legacy of laughter. In The 100 Greatest Silent Film Comedians, James Roots ranks the greatest performers based on a scorecard that measures each comic’s humor, timelessness, originality, and teamwork. Far more than just a listing, this is an idiosyncratic and entertaining review of the men and women who created the golden age of comedy. As a critic and deaf viewer, Roots brings a truly unique perspective to the evaluation of these performers and their work. He has viewed thousands of silent comedies and offers some assessments that run contrary to the standard list of performers. While many obvious names are placed in the top echelon, the author also champions performers who have been neglected, in part because their work has not been as visible. Each entry includes a filmography a scorecard an evaluation of the artist’s overall work an assessment of representative films DVD availability With the increased availability of films on DVD, as well as Internet access, more and more silent performers are being discovered by film fans. Supplemented by an appendix of comedians who missed the cut, as well as an annotated bibliography, The 100 Greatest Silent Film Comedians will be an invaluable resource to anyone wanting to know more about the brilliant entertainers of the silent era.